Images and/as Language in Nepal’s Older and Vulnerable Deaf Person’s Project - Erika Hoffmann-Dilloway (Semiotic Review, 2021)
Drawing on ethnographic research in Nepal’s Older and Vulnerable Deaf Person’s Project (ODP), this article explores the ways in which engagement with pictorial images in the ODP helped deaf elders cultivate the physical, semiotic, and pragmatic skills that underpin the reception and reproduction of conventionalized Nepali Sign Language (NSL) forms. This pedagogy emerged in part because local understandings of NSL as a named and objectified language have been grounded in pictorial illustrations of signers performing standardized lexical items in sign language dictionaries, posters, and primers. An analysis of an ODP session demonstrates how elders’ image-making practices in some cases worked to center their communicative practices on the standard lexical items in which local deaf sociality was grounded; in others cases it worked to exceed the relatively narrow view of NSL that these texts objectified. Analysis of these dynamics, along with my own use of pictorial images as a mode of generating, reflecting, and circulating analyses of language use, helps us consider the semiotic processes through which ideologies of image and language may be mutually constitutive, as well as how such a relationship can be regimented or unsettled.